A strategic plan paper for ACWS United Broadcasting Network, Inc. (WROCK FM) - Sinfuego, Sharlene Mae A.; Soledad, Miguel D.; Durana, Annalee D. (Davao City School of Management, University of the Philippines Mindanao, 2007)
The radio industry is now being challenged given the presence of numerous advertising media competing for scarce advertising money. ACWS United Broadcasting Network, Inc., popularly known as WRocK FM, is one of those broadcasting companies competing and surviving in a very fragmented industry. These challenges pushed the station to undertake a strategic planning exercise in order to know how to survive and win the battle. The following strengths and weaknesses were revealed during the internal environment analysis of the company: Strengths : Profitable; hits top 6 on radio survey; caters to the niche market and unique programming. Weaknesses: Centralized structure of management; low power input; poor communication and monitoring system; operates 16 hours a day compared to 24 hours of other radio stations. The analysis of its external environment revealed the following opportunities and threats: Opportunities: The internet; booming economies of the 3 cities; wider coverage; Filipinos? passion for music. Threats : Fragmented industry; other medium for advertising (TV, billboard, magazines, etc); deregulated rates/spot. Based on their analyses, the following objectives were formulated for 2008 to 2012: To increase its income by 20% in 2012; To be globally heard, reaching the Filipinos around the world via the internet in 2010; To capture the listeners belonging to the niche market around the world in 2012; and, To be the most visited internet radio website reaching 100 million visitors in 2012. To attain these objectives, two strategies are going to be implemented: to be an internet based radio station and to reformat some of its programs. These were formulated by juxtaposing the key environmental elements. An implementing program was crafted to put these strategies in place. Control systems were also created in order to ensure that WRocK FM reaches its goals during the forecast period.
Thesis, Graduate(Master in Management)--University of the Philippines Mindanao, December 2007
Keywords: Strategic plan